Diurnal changes of corneal epithelial and stromal thickness maps and visual quality in mild form of Fuchs' endothelial corneal dystrophy - Krolo, Iva; Bećirević, Aida Kasumović; Radman, Ivana; Kasumović, Armin; Matoc, Ines; Guarro, Idoia Goñi; Sabol, Ivan (Indian journal of ophthalmology, 2025)
Purpose: To investigate the functional and structural daily variations in eyes with a mild form of Fuchs' endothelial corneal dystrophy (FECD). Methods: This prospective study included 30 eyes with the mild form of FECD. Subjects underwent functional and structural testing at 8 AM, 2 PM, and 8 PM. Testing included measurement of uncorrected distance visual acuity (UDVA), best corrected twilight vision (TV), and contrast sensitivity function (CSF) testing (Vista Vision Far-Pola, DMD MedTech charts). Corneal epithelial and stromal parameters were evaluated with anterior segment optical coherence tomography (AngioVue, AvantiRTVue-XR; Optovue, CA, USA). Results: UDVA, TV, and CSF for spatial frequencies B, C, and F showed significant changes during the day, with the lowest values in the morning (P < 0.0001 for UDVA, P = 0.0109 for TV, and P < 0.0001, P = 0.0126, and P = 0.0471 for the three spatial frequencies, respectively). There was no significant change in epithelial parameters between visits. Central corneal thickness showed significant decrease during the day (P < 0.0001), as did the central stromal thickness on the 5- and 7-mm maps (P = 0.0002 and P < 0.0001, respectively), stromal thickness in the superior section of the 5-mm map (P = 0.0107), stromal thickness in the inferior section of the 7-mm map (P = 0.0002), and minimal stromal thickness on both maps (P < 0.0001). Conclusion: A significant negative correlation was found between central stromal thickness and TV, implying that simultaneous evaluation of corneal layers and visual quality may be useful in assessing FECD.